2019
DOI: 10.2174/2211536608666190314122725
|View full text |Cite
|
Sign up to set email alerts
|

TheKLF6Super Enhancer Modulates Cell ProliferationviaMiR-1301 in Human Hepatoma Cells

Abstract: Background: Recent studies have attempted to elucidate the function of super enhancers by means of microRNAs. Although the functional outcomes of miR-1301 have become clearer, the pathways that regulate the expressions of miR-1301 remain unclear. Objective: The objective of this paper was to consider the pathway regulating expression of miR- 1301 and miR-1301 signaling pathways with the inhibition of cell proliferation. Methods: In this study, we prepared the cell clones that the KLF6 super enhancer was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…found that heparinase eRNA enhances chromatin looping between the SE and promoter in several cancer cell lines, promoting tumorigenesis in vitro and in vivo [ 103 ]. Klf6 is a gene responsible for tumorigenesis, and the loss of the Klf6 SE was found to inhibit the proliferation of liver cancer cells by upregulating miR-1301 [ 104 ]. lncRNA HCCL5 is an SE-driven gene that confers the malignant phenotypes of liver cancer cells [ 105 ].…”
Section: Structures and Functions Of Sesmentioning
confidence: 99%
“…found that heparinase eRNA enhances chromatin looping between the SE and promoter in several cancer cell lines, promoting tumorigenesis in vitro and in vivo [ 103 ]. Klf6 is a gene responsible for tumorigenesis, and the loss of the Klf6 SE was found to inhibit the proliferation of liver cancer cells by upregulating miR-1301 [ 104 ]. lncRNA HCCL5 is an SE-driven gene that confers the malignant phenotypes of liver cancer cells [ 105 ].…”
Section: Structures and Functions Of Sesmentioning
confidence: 99%
“…In recent years, SE-derived ncRNAs have been found to play an important role in promoting the malignant proliferation of tumors ( Figure 3 ). Some SE-derived ncRNAs affect proliferation-related signaling pathways, thus leading to the unlimited proliferation of tumor cells 62 . Xie et al 63 reported a squamous cell carcinoma (SCC)-specific SE-derived lncRNA LINC01503.…”
Section: Role Of Se-derived Ncrnas In Cancermentioning
confidence: 99%
“…miRNAs are critical in preadipocyte adipogenesis, and KLF6 is also regulated by several miRNAs 13,[21][22][23][24] ; thus, we investigated whether the expression of KLF6 in FAPs was regulated by miRNAs. We analyzed several miRNAs that were reported to regulate adipogenesis.…”
Section: Klf6 Is the Target Gene Of Mir-22-3pmentioning
confidence: 99%